Development Model of Health Leaders for the Elderly - Chitmanasak, Nuttawadee (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
The development of health leaders for the elderly is intended to encourage the public sector to manage health to sustainably improve the quality of life of the elderly. The purpose of this research was to create and develop a model and test its effectiveness. The research was divided into two phases. Phase 1: Create and develop models with community leaders and village health volunteer leaders of Muang Khom Subdistrict, Chai Badan District, Lopburi Province, a total of 18 people. Phase 2: Test the effectiveness of the model. A sample group consisted of 38 village health volunteers. Data was collected using the health literacy scale and the satisfaction assessment form. Analyzing the data with average statistics, standard deviation, and a paired sample t-test. The results showed that the model was created and developed by applying the concepts of leadership development, health literacy based on the V-Shape model, and 5A. "Older people build cities" consists of 7 steps of operation, namely learning and understanding leadership empowerment according to the 5A and the V-Shape model in accessing, understanding, interacting with questions and exchanging knowledge, making decisions, changing behavior, and spreading the word, which has 34 activities. The efficacy test results were as follows: 1) Before the experiment, health leaders had high health knowledge according to the 5A principle. After the experiment, health knowledge reached its highest level. 2) compare the mean scores before and after the experiment; the mean score after the experiment was significantly higher than before the experiment at the.05 level. and 3) satisfaction with the style was at the highest level. The results of the study showed that the model had a high level of effectiveness. Therefore, the development model of health leaders for the elderly can be used to achieve results.